ANALISIS YURIDIS PENANGKAPAN IKAN OLEH KAPAL ASING YANG MENANGKAP IKAN DI INDONESIA - Abdullah Rafi; Endang Pandamdari (Reformasi Hukum Trisakti, 2023)
The main motivation behind this study is the great majority of foreign-flagged ships operating fishing operations in Indonesian seas without SIPI. The issue is how the Ministry of Maritime Affairs and Fisheries is authorized to enforce SIPI for foreign-flagged vessels conducting fishing operations in Indonesian waters, as well as how the Ministry is authorized to enforce SIPI for foreign-flagged vessels lacking SIPI, according to Court Decision No. 10/Pid.Sus/2018/Pn Tpg. The Ministry of Maritime Affairs and Fisheries will issue SIPI directives to the Director General of Fisheries for foreign-flagged vessels fishing in Indonesian seas. In this work, normative research methods, qualitative secondary data, and the Ministry of Maritime's authority were used. The finding is that the defendant lacks a license to engage in fishing activities in Indonesian waters and that the Minister entrusted to the Director General of Fisheries the authority to issue SIPI and amend Law No. 31 of 2004 concerning Fisheries.